The Dynamics of Social Identity in A Multicultural Society in Central Kalimantan - Sriyana Sriyana; Silvia Arianti (International Journal of Social Sciences, Language, and Education, 2026)
This study examines the dynamics of social identity within a multicultural society in Central Kalimantan through an empirical qualitative approach grounded in a descriptive-exploratory design. Data were collected through in-depth interviews, participant observation, and documentation analysis involving diverse ethnic groups, including Dayak, Banjar, Javanese, and Madurese communities. The findings reveal that social identity is continuously constructed through everyday interactions, negotiated within contexts of cultural difference and historical tension, and reconfigured through institutional mediation. Patterns of identity formation are shaped by symbolic practices and shared experiences, while negotiation processes reflect adaptive strategies to manage interethnic relations and mitigate conflict. Institutional actors, including educational, religious, and customary bodies, play a crucial role in stabilizing identity dynamics by fostering inclusive norms and redistributing symbolic power. The study contributes to theoretical discussions on social identity by demonstrating the interplay between micro-level interactions, meso-level negotiations, and macro-level institutional frameworks. It also highlights the importance of culturally embedded mechanisms and participatory governance in sustaining multicultural cohesion. These findings offer insights for policy development aimed at strengthening social integration in diverse societies